(untitled) (Journal Of Educational and Psychological Researches, 2017)
importumt educational institution as (kindergartens) need teachers which qualified ownes modalities in their education for children , as Marzanu method in a way of learning and own methods of crisis management, because the teachers that own those styles of learning ginekindergarten children knowledge and the childrenIeaving based on theMeaing and knowledge and integration of their information, And teachers that earn methods of crisis management provide for the children of the kindergarten security within the educational institution which in turn affect the growth and development of the Child and then abilities, health physical, mental, psychological …etc.., The aims of the current research have identified to recognize: 1- the dimensions for Marzanuof learningfor kindergartenteachers according to the five dimensions (trends positive and perceptions toward learning, knowledge acquisition and its integration, deepening the knowledge and refined meaningful, use of the knowledge, habits ofproductive mind). 2-the methods of crisis management for kindergarten teachers according to the four methods (initial study of the dimensions of the crisis, the analytical study of the crises, scientific planning to deal with the crisis, the actual intervention to face the crisis). 3. The relationship between the dimensions of learning for Marzanumethods in crisis management for kindergartenteachers . The current research Is defined by : 1.the governmentkindergarten related to the six educationdirectordes in Baghdad city both side (Al Karakh and Al rosafa). 2. The teachers exited in a kindergarten in the city of Baghdad in the sixdirectorates of the education both (Al Karakh and Al rosafa). 3. The Academic Year (2015- 2016). In order to achieve the objectives of the search the sample of kindergarten teachers in the city of Baghdad is cosist of (400), the teacher to answer the gauge babysitting where they selected randomly simple way form (51)kindergarten distributed in six Education directorates, and to measure learning dimensions for Marzanuand its relationship to the methods of crisis management researcher sought to : building Measure mat (dimensions of Marzanulearning)according to five dimensions (trends positive and perceptions toward learning, knowledge acquisition integration, deepening the knowledge and refined meaningful, use the of knowledge, habits of mind) and building et methods of crisis management in product four methods are ( the initial study of the dimensions of the crisis, the analytical study of the crises, scientific planning to deal with the crisis, the actual intervention to face the crisis), These twomeasurementexperts a group of twenty two experts with scientific in kindergarten and measurement and evaluation and educational administration for the two measurement to demonstrate the validity of the paragraphs of the measurement and the researcher used two indicators of the truth, (the apparent Trueness and trueness of construction) whilemeasurement the stability standards of had extracted by researcher for each measurement of two types of stability the coefficient of stability the measurement of dimensions of MR learning in a re-testing is (0.79)andAlfa Cronbachmanner is (0.86) andstability of the measurement methods of crisis management in a manner re-testing (0,74)and the way Alfa Cronbach(0,84). In the measurement objectives of the current research after the application of the to the sample and analysis of their responses statistically using Ttest onesamples and Pearson correlation coefficient and the research conclue the following results: 1. The teachers of the kindergarten using the dimensions of the five learning in the MR model (that includes several educational theories in its model such as Piaget theory representation in harmonizing the Cooperative Learning based on problems OZBELtheory is on and use the reward and training and feedback. 2. All the teachers of the kindergarten this country the four methods of management of the crises in general way as a result of the circumstance of unstable security, which requires know all methods of management of crises within the kindergarten or outside it. 3. The teachers that use the dimensions of the five learning MR also have the methods of crisis management because of availability of analytical side of thought and knowledge related on that help the teachers to reinvent modern methods in the management of the crises that may bethe teachers exposed within the kindergarten or outside it. In light of these results, the researcher putsomeimportant andrecommendationssuggests